2023
DOI: 10.3390/cells12060858
|View full text |Cite
|
Sign up to set email alerts
|

Black Poplar (Populus nigra L.) Root Extracellular Trap, Structural and Molecular Remodeling in Response to Osmotic Stress

Abstract: The root extracellular trap (RET) consists of root-associated, cap-derived cells (root AC-DCs) and their mucilaginous secretions, and forms a structure around the root tip that protects against biotic and abiotic stresses. However, there is little information concerning the changes undergone by the RET during droughts, especially for tree species. Morphological and immunocytochemical approaches were used to study the RET of black poplar (Populus nigra L.) seedlings grown in vitro under optimal conditions (on a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 90 publications
0
1
0
Order By: Relevance
“…For the tissular tool, we investigated the immunolocalization of plant glycopolym epitopes, as there is clearly a close relationship between cell wall glycomolecules and otic stress [54]. Indeed, drought stress affects cell wall composition in terms of pect hemicelluloses, and hydroxyproline rich glycoproteins (HRGP) [55,56]. Thus, our res showed that under drought stress conditions, application of Musa leachate induces modeling of glycopolymers labeling only in mature tomato stems.…”
Section: Paradisiaca Leachate As a Biostimulantmentioning
confidence: 95%
“…For the tissular tool, we investigated the immunolocalization of plant glycopolym epitopes, as there is clearly a close relationship between cell wall glycomolecules and otic stress [54]. Indeed, drought stress affects cell wall composition in terms of pect hemicelluloses, and hydroxyproline rich glycoproteins (HRGP) [55,56]. Thus, our res showed that under drought stress conditions, application of Musa leachate induces modeling of glycopolymers labeling only in mature tomato stems.…”
Section: Paradisiaca Leachate As a Biostimulantmentioning
confidence: 95%